Automatización de los procesos de soldadura final para vehículos de pasajeros en GM Colmotores (2016)
The following article shows how challenges caused by marketing conditions in the auto manufacturing industry have generated the necessity to convert the development of technology into a continuous process. This necessity drives competitiveness. In this document, there is a brief description of the concepts related to industrial automation, an assessment of automotive assembly processes, and variables to be evaluated and controlled in order to better plan automated projects based on robotic welding. Additionally, a brief revision of the automated processes of welding is provided with the latest technology and industry trends in mind. The application of an automated welding process as part of a Technological Development project is presented, which after being applied on an industrial level at GM Colmotores, generated positive results in the processes of ergonomics, manufacturing, and quality.